2021
DOI: 10.3389/fnhum.2021.717291
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Potential of Virtual Walking Techniques for Gait Rehabilitation

Abstract: Virtual reality (VR) technology has emerged as a promising tool for studying and rehabilitating gait disturbances in different cohorts of patients (such as Parkinson's disease, post-stroke, or other neurological disorders) as it allows patients to be engaged in an immersive and artificial environment, which can be designed to address the particular needs of each individual. This review demonstrates the state of the art in applications of virtual walking techniques and related technologies for gait therapy and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 169 publications
(187 reference statements)
0
7
0
Order By: Relevance
“…Technologies that provide visual information and feedback include head-mounted displays (HMD), monitors, or large screen projectors (e.g., cave automatic virtual environment, CAVE) to create partially or fully immersive environments (Bishop and Fuchs, 1992 ; Milgram et al, 1995 ). Some studies support the use of fully immersive virtual reality (VR) for walking rehabilitation (Borrego et al, 2016 ; Janeh and Steinicke, 2021 ). These virtual environments rely on “walking-in-place” or “redirected walking” strategies to emulate features of the real world.…”
Section: Introductionmentioning
confidence: 99%
“…Technologies that provide visual information and feedback include head-mounted displays (HMD), monitors, or large screen projectors (e.g., cave automatic virtual environment, CAVE) to create partially or fully immersive environments (Bishop and Fuchs, 1992 ; Milgram et al, 1995 ). Some studies support the use of fully immersive virtual reality (VR) for walking rehabilitation (Borrego et al, 2016 ; Janeh and Steinicke, 2021 ). These virtual environments rely on “walking-in-place” or “redirected walking” strategies to emulate features of the real world.…”
Section: Introductionmentioning
confidence: 99%
“…The VR rehabilitation was found to improve gait and balance significantly. 51 , 52 , 53 The VR produced a similar impact on long- and short-term effects on gait and balance. 43 , 54 Moreover, VR training exercises reduced the risk of falls.…”
Section: Gait and Balance In Pd And Exercisementioning
confidence: 90%
“…Furthermore, Janeh et al reported that VR might improve the gait of persons with neurological disorders after experiencing it. As a result of their observations, they stressed the importance of using virtual walking approaches in rehabilitation [31].…”
Section: Gait Improvement After Vr Interventionmentioning
confidence: 96%